Ascorbic acid loss, microbial spoilage and sensory changes in aonla juice during storage (Indian Journal of Arid Horticulture, 2025)
Being acidic and astringent in taste and perishable in nature the potential of aonla for preparation of vitamin C rich beverages has been explored on. In present endeavor attempt was made to study the effect of pasteurization, sulphitation in combination with different storage conditions so as to draw inference as to how long the quality of aonla juice stands intact. Sulphitation (350 ppm SO,) of aonla juice coupled with storage at low temperature minimized the loss of vitamin 'C' and produce best sensory quality even after six months of storage. Pasteurization and sulphitation both inhibited the yeast growth throughout the storage period and thus helped extend the storability of aonla juice. Key words: Ascorbic acid, aonla, juice, pasteurization, storage, sulphitation
Keywords: Ascorbic acid; aonla; juice-; pasteurization; storage; sulphitation